Transcriptional Analysis of Human Skin Lesions Identifies Tryptophan-2,3-Deoxygenase as a Restriction Factor for Cutaneous Leishmania - Rodrigues, Vasco; André, Sónia; Maksouri, Hasnaa; Mouttaki, Tarik; Chiheb, Soumiya; Riyad, Myriam; Akarid, Khadija; Estaquier, Jérôme (Frontiers in Cellular and Infection Microbiology, 2019)
Disease manifestation after infection with cutaneous Leishmania species is the result of a complex interplay of diverse factors, including the immune status of the host, the infecting parasite species, or the parasite load at the lesion site. Understanding how these factors impact on the pathology of cutaneous leishmaniasis (CL) may provide new targets to manage the infection and improve clinical outcome. We quantified the relative expression of 170 genes involved in a diverse range of biological processes, in the skin biopsies from patients afflicted with CL caused by infection with either L. major or L. tropica. As compared to healthy skin, CL lesions bear elevated levels of transcripts involved in the immune response and, conversely, present a significant downregulation in the expression of genes involved in epidermal integrity and arginine or fatty acid metabolism. The expression of transcripts encoding for cytotoxic mediators and chemokines in lesions was inversely correlated with the expression of genes involved in epidermal integrity, suggesting that cytotoxicity is a major mediator of CL pathology. When comparing the transcriptional profiles of lesions caused by either L. major or L. tropica, we found them to be very similar, the later presenting an aggravated inflammatory/cytotoxic profile. Finally, we identified genes positively correlated with the parasite load in lesions. Among others, these included Th2 or regulatory cytokines, such as IL4 or IL10. Remarkably, a single gene among our dataset, encoding for tryptophan-2,3-deoxygenase (TDO), presented a negative correlation with the parasite load, suggesting that its expression may restrict parasite numbers in lesions. In agreement, treatment of human or mause macrophages infected with L. major in vitro with a TDO inhibitor led to an increase in parasite transcripts. Our work provides new insights into the factors that impact CL pathology and identifies TDO as a restriction factor for cutaneous Leishmania.